Financial Liberalization, Credit Constraints, and Collateral : Investment in the Mexican Manufacturing Sector - Gelos, R. (IMF Working Papers; Working Paper, 1999)
This paper examines the impact of financial liberalization on fixed investment in Mexico, using establishment-level data from the manufacturing sector. It analyzes changes in cash-flow sensitivities and uses an innovative approach to explore the role of real estate as collateral and deal with a potential censoring problem. The results suggest that financial constraints were eased for small firms but not for large ones. However, banks' reliance on collateral in their lending operations increased the importance of real estate. The results provide microeconomic evidence consistent with the role attributed to 'financial accelerator' mechanisms during lending booms and during recessions that stem from financial crises.